Pengembangan Sistem Pengelolaan Lembar Kerja Anggaran Investasi pada Program Rencana Kerja Trafo Sisipan dan Jaringan Penunjang PLN Berbasis Web (Studi Kasus PT PLN (Persero) UP3 Malang) - Tri Purwanti; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Work Plan Program of Inserted Transformer and Support Network in Investment Budget Worksheet is an investment job proposal to propose inserted transformer and support network at PT PLN (Persero) UP3 Malang. PT PLN (Persero) UP3 Malang has been managing the proposal data of such work plan program manually using Microsoft Office Excel with separated data support. It causes duplication on the proposal data after being checked and revised, difficulties to change the price of construction which has undergone uncertain revision. Further, the Customer Service Unit (ULP) doesn't always know the progress of the submitted proposal. Investment Budget Worksheet Management system for Work Plan Program of Inserted Transformer and Support Network has been developed as a solution to solve such problems. The system was developed in a web-based platform and a waterfall development model. This system is expected to help PT PLN (Persero) UP3 Malang in managing the proposal data of Work Plan Program of Inserted Transformer and Support Network. This system has been tested using white-box testing technique for unit and integration testings, and black-box testing technique for validation testing. Unit and integration testings has been done on 3 samples method and passed validation testing on 54 functional requirements which give valid results.